Anthropotropism: Searching for Recognition in the Scandinavian Gig Economy - Newlands, Gemma (Sociology (Oxford), 2022)
By curtailing workplace socialisation, platform-mediated gig work hinders the development of affective relationships necessary for the experience of recognition. However, extant research into recognition at work has typically only focused on face-to-face interactions, overlooking technologically complex forms of work where recognition might be sought from and via technical intermediaries. Advancing sociological research into the lived experience of contemporary gig workers, this article draws on 41 interviews with Foodora riders in Norway and Sweden to explore how gig workers solicit and experience recognition at work. I identify a process of anthropotropism, whereby gig workers turn to human connections where possible in an attempt to pursue traditional social scripts of collegiality and to gain recognition from legitimate human sources. Further, I identify how platform-mediated communication does not prohibit recognition, but intermittent automation and neoliberal modes of instrumentalising recognition can disrupt the development of individual subjectivities and lead to feelings of mechanistic dehumanisation.